Cyclopentanone Derivatives from 5‐Hydroxymethylfurfural via 1‐Hydroxyhexane‐2, 5‐dione as Intermediate. Issue 2 (29th December 2017) - Wozniak, Bartosz; Spannenberg, Anke; Li, Yuehui; Hinze, Sandra; de Vries, Johannes G.
Abstract: An efficient strategy for the conversion of biomass derived 5‐hydroxymethylfurfural (HMF) into 2‐hydroxy‐3‐methylcyclopent‐2‐enone (MCP) by an intramolecular aldol condensation of 1‐hydroxyhexane‐2, 5‐dione (HHD) has been developed. Further transformations of MCP towards the diol, enol acetate, levulinic acid and N‐heterocyclic compounds are also reported. Abstract : Dione and dusted : An efficient strategy for the conversion of biomass‐derived 5‐hydroxymethylfurfural into 2‐hydroxy‐3‐methylcyclopent‐2‐enone (MCP) by an intramolecular aldol condensation of 1‐hydroxyhexane‐2, 5‐dione has been developed. Further transformations of MCP into the diol, enol acetate, levulinic acid, and N‐heterocyclic compounds are also reported.